REPRODUCTIVE RESPONSE OF RABBITS FED SUPPLEMENTALMoringaoleifera (Lam) LEAF MEAL (2014)
Reproductive inefficiency is a major challenge in rabbit production. Leaf meals such as Moringaoleiferarich in phytochemicals have been used to enhance reproductive performance in cattle and catfish. Information on the use of MoringaoleiferaLeaf Meal (MoLM) to enhance reproductive efficiency in rabbits and its effect on organs has not been adequately documented. Therefore, the reproductive response of rabbits to supplemental MoLM was assessed.In a 24-week trial, sixty rabbits were allotted to four diets containing supplemental MoLM : 0 (control), 2.5, 5.0 and 7.5%with 10 does and 5 bucks per treatment. Dry Matter Intake (DMI, g) and Daily Weight Gain (DWG, g) were determined. Blood (5.0 mL) was sampled from bucks and does for Haematology (Erythrocytes, x103mm-3, Packed Cell Volume (PCV, %), haemoglobin, g/100 ml), Alanine amino Transferase (ALT, IU/L) and hormonal (testosterone, oestrogen) assay using standard procedures.Bucks were assessed for semen characteristics and then assigned to does on each treatment at 2 does/buck for mating trial using standard procedures. Blood (3mL) was sampled from pregnant does at third trimester for progesterone determination using standard procedures. Conception Rate (CR), Gestation Length (GL), Litter Size (LS) and Litter Weight (LW) were determined using standard procedures. Testes and epididymides were removed, weighed and processed for sperm reserves (x106sperm cells/ml). Histopathology (no visible lesion, mild, moderate, severe and very severe) of liver, kidney and ileum was assessed using standard procedures. Data were analysed using descriptive statistics, polynomial regression and ANOVA at α0.05. The DMI was not significantly different among the treatments. The DWG of rabbits on control (6.3±0.8), 2.5% (5.2±0.4) and 5.0% (5.2±0.5) MoLM were higher than those fed 7.5% (4.4±0.4). Erythrocytes (6.8±0.2), PCV (40.2±1.6) and Hb (13.0±0.5) were higher in rabbits fed 2.5% MoLM. The ALT of rabbits on control (19.2±2.0) was significantly lower than those on MoLM diets (38.7±4.2 – 48.2±2.7). Oestrogen values ranged from 16.5±1.2 to 25.8±2.0 ng/L and was higher in rabbits fed MoLMthan those on control (10.0±0.8ng/L). Progesterone levels were higher in rabbits on MoLM diets ranging from 1.8±0.4 to 2.8±0.4 ng/L than those on the control (0.63±0.1ng/L). Serum testosterone level was not significantly different among the treatments. Sperm motility (90.3±0.2%), mass activity (3.0±0.01), live sperm cells (88.5±3.4%) and CR (100.0%) of rabbits fed 2.5% MoLM were higher than those rabbits on other treatments. The GL, LS, and LW were not significantly different among the treatments. Testicular sperm reserves ranged from 14.0±1.5 to 53.0±11.1,while epididymal sperm reserves were not significantly different among the treatments. Histopathology of liver, kidney and ileum indicated moderate necrotic lesions at 5.0 and 7.5 % MoLM. Regression of sperm motility on MoLM levels in bucks indicated an optimum inclusion level of 2.7% (R2=0.56) while regression of conception rate on MoLM levels in does showed an optimum inclusion level of 2.5% (R2=0.61).